If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 4(-1m + 2) = m + 16 Reorder the terms: 3 + 4(2 + -1m) = m + 16 3 + (2 * 4 + -1m * 4) = m + 16 3 + (8 + -4m) = m + 16 Combine like terms: 3 + 8 = 11 11 + -4m = m + 16 Reorder the terms: 11 + -4m = 16 + m Solving 11 + -4m = 16 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. 11 + -4m + -1m = 16 + m + -1m Combine like terms: -4m + -1m = -5m 11 + -5m = 16 + m + -1m Combine like terms: m + -1m = 0 11 + -5m = 16 + 0 11 + -5m = 16 Add '-11' to each side of the equation. 11 + -11 + -5m = 16 + -11 Combine like terms: 11 + -11 = 0 0 + -5m = 16 + -11 -5m = 16 + -11 Combine like terms: 16 + -11 = 5 -5m = 5 Divide each side by '-5'. m = -1 Simplifying m = -1
| 9y^2-27y+36= | | 10b-10=20 | | 4/5x+y=27 | | 5x-4=-x-2 | | 5x-4=-c-2 | | a^4-1= | | 4(x-6)=-6 | | X+20=5-x | | 220=-4+8P | | 2xy-6x= | | 36x^2-96x+36=0 | | 4(n+20)=100 | | 4(n+20)=4n+80 | | 4(n+20)=4n+20 | | 26x^2-36y^2=81 | | 314/75(7.75)^3 | | 6-y=-6 | | 4/3*3.14(7.75)^3 | | 253-5x=40x+17 | | 15-9x=2x-7 | | 3x^2-5x+2y-4=0 | | 3y/6 | | (-5)-(-8)-4y+(-4x)-(-7y)-(-10x)= | | 77+5(x+9)=x | | 9x-(-7y)-(-6)+9-(-2x)-4y= | | (-x)-(-6)+(-4x)+(-7y)-1-8y= | | (-8)+(-8x)+(-y)+4+(-x)+(-9y)= | | -4a^3*2b^2= | | (-8y)-1+y+(-x)-3x-(-8)= | | 10x^24=56 | | 6x-293=6x-13 | | 3y+4+6x-3x-2y-2= |